Impact of the 2007 US financial crisis on the emerging equity markets - Abdul Majid, M. Shabri; Kassim, Salina (Emerald Group Publishing Limited, 2009)
The purpose of this paper is to explore empirically the effects of the current financial crisis on the integration and co-movements of selected stock markets of the emerging economies, namely Indonesia and Malaysia.